PENGARUH KUALITAS SUMBER DAYA MANUSIA, DISIPLIN KERJA, DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN UMKM - Magdalena Lintang Firdaus; Lina Susilowati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze the effect of human resource quality, work discipline, and work motivation on employee performance at the tofu UMKM in Kebontemu Village. This research uses a quantitative approach with multiple linear regression analysis method. The population in this study were all employees of three tofu factories in Kebontemu Village totaling 100 employees, with a sample of 80 respondents determined using the Slovin formula and proportional random sampling technique. Data were collected through questionnaires, observation, interviews, and documentation. The results showed that: Human resource quality has a positive and significant effect on employee performance with t-count of 15.742 and significance of 0.000;, work discipline has a positive and significant effect on employee performance with t-count of 12.831 and significance of 0.000;, work motivation has a positive and significant effect on employee performance with t-count of 3.448 and significance of 0.001;, simultaneously, human resource quality, work discipline, and work motivation have a positive and significant effect on employee performance with F-count of 693.900 and significance of 0.000. The coefficient of determination (R²) value of 0.965 indicates that 96.5% of the variation in employee performance can be explained by the three independent variables.